Analisis Implementasi Peraturan Bupati Empat Lawang Nomo 47 Tahun 2018 tentang Pesta Rakyat (Studi Kasus di Kecamatan Sikap Dalam Kabupaten Empat Lawang Perspektif Hukum Islam) - Adha, Idul (UIN Fatmawati Sukarno Bengkulu, 2022)
Abstract : The implementation of the Empat Lawang Regent Regulation Number 47 of 2018 concerning the People’s Party in the Attitude District of Empat Lawang Regency has gone well even though at the beginning of the implementation of the ban on parties at night there were some groups of people who challenged the implementation of the ban on parties at night. The supporting factor in the Regent’s Regulation Number 47 of 2018 concerning the People’s Party is the coordination through routine meeting activities carried out by the enforcement team for banning parties at night. There is community participation through reporting activities in case of party violations at night. There is a commitment through the Integrity Fact Signing carried out by the party ban enforcement team at night. Whereas the implementation of the Empat Lawang Regent Regulation Number 47 of 2018 concerning the People’s Party in the Attitude District of Empat Lawang Regency, the Islamic Political perspective has followed the recommendations of the Islamic Religion, contains 4 guidelines in carrying out political leadership. Keywords: Implementation, Regent Regulation, People’s Party. Abstrak : Implementasi Peraturan Bupati Empat Lawang Nomor 47 Tahun 2018 tentang Pesta Rakyat di Kecamatan Sikap Dalam Kabupaten Empat Lawang sudah berjalan dengan baik walaupun diawal pemberlakuan larangan pesta dimalam hari ada sebagian golongan masyarakat yang menantang diberlakukannya larangan pesta dimalam hari. Faktor Pendukung dalam Peraturan Bupati Nomor 47 Tahun 2018 tentang Pesta Rakyat adalah, adanya koordinasi melalui kegiatan rapat rutin yang dilakukan oleh tim penegak larangan pesta dimalam hari. Adanya partisipasi masyarakat melalui kegiatan laporan apabila terjadi pelanggaran pesta dimalam hari. Adanya komitmen melalui Penandatanganan Fakta Integritas yang dilakukan oleh tim penegak larangan pesta dimalam hari. Bahwa implementasi Peraturan Bupati Empat Lawang Nomor 47 Tahun 2018 tentang Pesta Rakyat di Kecamatan Sikap Dalam Kabupaten Empat Lawang perspektif Politik Islam sudah mengikuti anjuran Agama Islam, telah mengandung 4 tuntunan dalam melaksanakan kepemimpinan politik. Kata Kunci:Implementasi, Peraturan Bupati, Pesta Rakyat